PROMOSI PRODUK DI MEDSOS MELALUI BEKAL DESAIN MARKETING ONLINE - Nurmalya Kardina, Rizki; Wijayanti, Lono; Abidatun Mu’awanah, Nurul; Chaiyun Nafiah, Ilmi; As’ad Awalludin, Muhammad; Eka Pratama, Ahmad Yudha (Jurnal Akselerasi Merdeka Belajar dalam Pengabdian Orientasi Masyarakat (AMPOEN): Jurnal Pengabdian kepada Masyarakat, 2024)
Along with the development of digital technology, social media has become an effective platform for promoting products and services. This KKN aims to empower the community in Tanjungan village to be able to utilize the potential of social media in marketing local products. By providing online marketing design training, it is hoped that people can increase the selling value of their products and open up wider market opportunities. It is hoped that this activity can contribute to increasing sales and growth of UMKM in the region.